2010
DOI: 10.3109/08958378.2010.527398
|View full text |Cite
|
Sign up to set email alerts
|

Exposure–response effects of inhaled sulfur mustard in a large porcine model: a 6-h study

Abstract: These findings are consistent with those seen in the early stages of acute lung injury (ALI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…In regard to other animal models, when ethanolic SM vapor was delivered to glass catheter-intubated rats, the same type of injury in the conducting airways occurred, with fibrin-containing casts present in the bronchi and bronchioles (39). In the porcine SM model, where high-dose SM was delivered as a neat vapor via nasal inhalation, gas exchange abnormalities mirroring our findings were noted, but more importantly, airway-obstructive lesions caused mortality in 40% of the pigs in less than 6 hours from initial SM exposure (40). Thus, an injury affecting the conducting airways has been reported in both humans and animal models of SM inhalation, just as we have found in our CEES inhalation model.…”
Section: Discussionsupporting
confidence: 50%
“…In regard to other animal models, when ethanolic SM vapor was delivered to glass catheter-intubated rats, the same type of injury in the conducting airways occurred, with fibrin-containing casts present in the bronchi and bronchioles (39). In the porcine SM model, where high-dose SM was delivered as a neat vapor via nasal inhalation, gas exchange abnormalities mirroring our findings were noted, but more importantly, airway-obstructive lesions caused mortality in 40% of the pigs in less than 6 hours from initial SM exposure (40). Thus, an injury affecting the conducting airways has been reported in both humans and animal models of SM inhalation, just as we have found in our CEES inhalation model.…”
Section: Discussionsupporting
confidence: 50%
“…Apoptosis is believed to have contributed to the lung injury in Iranian victims of SM exposure [43]. Increased LDH activity (cell death) was observed in guinea pig lungs [44] and tracheal epithelial cells of pigs exposed to SM inhalation [45]. If the cell injury/death involves an apoptotic process, the nuclear condensation of apoptotic cells can be visualized by TUNEL staining [46].…”
Section: Discussionmentioning
confidence: 99%
“…Anderson et al (1996) described the pathogenesis of HD-induced lesions in the rat respiratory tract. More recent studies in the pig model, Fairhall et al (2010) found significant changes in shunt fraction from 3 to 6 hours post-exposure, increased hypoxia, respiratory acidosis, and pathological finding of necrosis and erosions in the tracheal epithelium.…”
Section: Introductionmentioning
confidence: 88%